Designing A Computer Network At Sman 10 Kota Bengkulu With Bandwidth Management Web-Based Computer Network And Hybrid Topology - Poppy Septea Utami; Toibah Umi Kalsum; Yessi Mardiana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The computer network at SMAN 10 Kota Bengkulu is currently connected to the internet network, the utilization of the LAN network, especially the internet at SMAN 10 Kota Bengkulu has not been maximized, because there are still frequent network disruptions such as slow networks that cause many sites that cannot be opened when many users. This study aims to conduct web-based bandwidth management using Mikrotik at SMAN 10 Kota Bengkulu. The study used an experimental method. With the existence of Mikrotik-based network management, it is expected to smooth the network. So that the benefits of the network can be felt by users of SMAN 10 Kota Bengkulu. Bandwidth management at SMA N 04 Kota Bengkulu can be done via the web, with one user name only being able to access the network on one device, bandwidth management with this web will produce an account according to the account profile, bandwidth management is done using the web. After managing bandwidth using a Mikrotik-based web at SMAN 10 Bengkulu City, the network can run stably and well, namely with throughput results = 4.06, Average delay = 0.648, jitter = 0.018 and Packet Lost = 0%.